The Impact of Dhuha Prayer on Students' Emotional Intelligence: A Management Perspective in School Settings - Marwani; Yashofia Siti Zahro (Journal of Educational Management Research, 2025)
Emotional intelligence (EI) is increasingly recognized as a vital factor in students’ academic success and personal development. This study investigates the impact of Dhuha prayer on the emotional intelligence of middle school students from a management perspective. The purpose of this study was to examine the effects of regular Dhuha prayer engagement on the five key components of emotional intelligence: self-awareness, self-regulation, motivation, empathy, and social skills. A mixed-methods approach was employed, including pre- and post-test surveys, interviews, classroom observations, and document analysis. The study involved 100 students, divided into an experimental group (who participated in the Dhuha prayer program) and a control group (who did not). The results revealed that the experimental group showed significant improvements in EI, especially in self-regulation and self-awareness, with an increase of 15.9 points. In contrast, the control group showed minimal changes. These findings highlight the positive effects of Dhuha prayer on students’ emotional intelligence, suggesting that integrating spiritual practices in school management can foster emotional and social development. This research contributes to the understanding of the role of spiritual practices in educational management and provides a foundation for further exploration of these practices in enhancing student well-being and performance.